Un’architettura ’autre’: l’allestimento per la mostra ’Moda Stile Costume’ a ’Italia ’61’ - Ghoddousi, Leone Carlo (Opus Incertum, 2024)
Organized as part of the international exhibition Italia ’61 with the aim of offering the public a reflection on the evolution of Italian society over the preceding sixty years, the exhibition Moda Stile Costume was distinguished by an evocative setting designed by architects Roberto Gabetti, Aimaro Isola, Giorgio Raineri and Augusto Cavallari Murat, in collaboration with the sculptor Franco Garelli. The design proposal featured a free composition of veils, in dialogue both with the concrete shell-roof of the Palazzo delle Mostre and with the environmental installations conceived by Franco Garelli. This approach allowed the architects to address the vast interior space of the building while capturing the playful and ironic spirit of the exhibition and its contents. A nuanced interpretation of the alternating souls of post-war Turin – where the scientific rigor of industrial expansion coexisted with the whimsical impulses of its peculiar intellectual milieu – the exhibition represents the result of a collaborative effort that involved architects, intellectuals, artists, and entrepreneurs. In doing so, it offered a cross-section of Turin’s cultural life during the Italian economic miracle.